Clinical Profile of Status epilepticus (SE) in Children in a Tertiary Care Hospital in Bihar - Kumar, Mritunjay (JCDR Research and Publications (P) Limited, 2014)
Background: Status epilepticus (SE) is a common, life threatening neurologic disorder that is essentially an acute, prolonged epileptic crisis. SE can represent an exacerbation of a pre-existing seizure disorder, the initial manifestation of a seizure disorder, or an insult other than a seizure disorder. Objectives: To study the aetiology, clinical profile, and outcome of SE in pediatric age group. Setting and study design: Prospective study at a tertiary care medical college hospital in Bihar, India. Materials and methods: Study was carried out for a period of one year (from April 2008 to March 2009). Seventy patients of SE in the age group of six month to 12 years were included in the study. Clinical history, general and systemic examination and relevant investigations along with pretested questionnaire were used to categorise different variables. Independent t-test was used for continuous variables and chi-square test for categorical variables. Results: Mean age for the study population was found to be 5.94 years (SD=3.152). Preponderance of male (60%) over female (40%) was observed. Aetiology included Idiopathic (27.14%), remote symptomatic (20%), acute symptomatic (47.14%), febrile (2.86%) and progressive encephalopathy (2.86%) groups. Generalised tonic clonic convulsion (GTC) convulsion was observed in 91.4% of SE patients while 8.6% had partial SE. Eighteen patients (25.7%) had prior history of convulsion whereas 52 patients (74.3%) presented with SE as first episode of convulsion. In our study, mortality rate was found to be 31.4% and acute symptomatic causes were responsible for most of the deaths. Conclusion: SE is a severe life threatening emergency with substantial morbidity and mortality. Patients with younger age and male sex are slightly more vulnerable to develop SE. Longer duration of SE and acute symptomatic aetiologies are independent predictors for poor outcome.